Ginsenoside Rb1 protects human vascular smooth muscle cells against resistin-induced oxidative stress and dysfunction - Lu, Weifeng; Lin, Yue; Haider, Nezam; Moly, Pricila; Wang, Lixin; Zhou, Wei (Frontiers in Cardiovascular Medicine, 2023)
Resistin has been shown to play a key role in inducing vascular smooth muscle cells (VSMCs) malfunction in the atherosclerosis progression. Ginsenoside Rb1 is the main component of ginseng, which has been used for thousands of years and has been reported to have a powerful vascular protective effect. The aim of this study was to explore the protective effect of Rb1 on VSMCs dysfunction induced by resistin. In the presence or absence of Rb1, human coronary artery smooth muscle cells (HCASMC) were treated at different time points with or without 40 ng/ml resistin and acetylated low-density lipoprotein (acetylated LDL). Cell migration and proliferation were analyzed using wound healing test and CellTiter Aqueous Cell Proliferation Assay (MTS) test, respectively. Intracellular reactive oxygen species (ROS) (H2DCFDA as a dye probe) and superoxide dismutase (SOD) activities were measured by a microplate reader and the differences between groups were compared. Rb1 significantly reduced resistin-induced HCASMC proliferation. Resistin increased HCASMC migration time-dependently. At 20 µM, Rb1 could significantly reduce HCASMC migration. Resistin and Act-LDL increased ROS production to a similar level in HCASMCs, while Rb1 pretreated group reversed the effects of resistin and acetyl-LDL. Besides, the mitochondrial SOD activity was significantly reduced by resistin but was restored when pretreated with Rb1. We confirmed the protection of Rb1 on HCASMC and suggested that the mechanisms involved might be related to the reduction of ROS generation and increased activity of SOD. Our study clarified the potential clinical applications of Rb1 in the control of resistin-related vascular injury and in the treatment of cardiovascular disease.